Developing a Performance-Based Approach to the Effect of Roof Features on Fire Safety in Buildings with Atriums (International Journal of Built Environment and Sustainability, 2023)
Developing technology, changing social structures, and the threat of resource depletion have changed the design of buildings. Therefore, design approaches are developed to increase user comfort and reduce energy consumption by utilizing natural ventilation and lighting. The design of the distribution of outdoor air and light into the spaces through vertical and horizontal gaps reduces the energy demand of the mechanical systems and increases occupant comfort. The atrium is the preferred vertical gap in modern buildings for distributing natural air and light to interior spaces under appropriate conditions.  However, in buildings with atrium, there is a risk of fire spreading in the event of a fire due to the uninterrupted gaps between the rooms. It is necessary to ensure the operability of the design by monitoring the measures to be taken in the early stages of design using performance-based fire safety methods. This study develops design strategies for fire analysis in atrium buildings using computational fluid dynamics (CFD) simulation technology. Atrium height, roof type, and slope characteristics are analyzed for the stack effect, which is the main factor in the movement of smoke and flames. As a result of the numerical analyses consisting of flat, unidirectional, and bidirectional sloping roof type, 10, 20, 30-degree roof slope, and one-meter rising atrium roof variables, the effect degrees for smoke dispersal and temperature control are investigated. Fire Dynamic Simulator, which uses CFD capabilities, and Smokeview software, which can visualize the results, were used for the numerical analysis. Correlation analysis was used to determine the effect of variables on temperature. The results showed that flat roofs and designs with increasing height were effective in delaying the spread of smoke and increasing the stack effect in the atrium, while the contribution of roof slope to fire safety was weak.
Keywords: Atrium, Fire safety, Performance - based approach, Roof features, Computational fluid dynamics